Fixed Point Theorems of Ćirić-Type Contraction - Chiroma, Rhonda; Tanto, Ezra Emmanuel (Darul Yasin Al Sys, 2025)
This paper introduces a novel class of Ćiríc-type contraction operators within the framework of complete metric-like spaces. The study establishes sufficient conditions under which fixed points exist for such mappings, expanding the theoretical foundation of fixed point theory. A carefully constructed, non-trivial comparative example is provided to illustrate the broader applicability and generality of the main result. Furthermore, several corollaries are derived, demonstrating that the proposed theorem not only encompasses but also unifies numerous existing fixed point theorems associated with Ćiríc-type contractions. The findings contribute to a deeper understanding of generalized contractive mappings and offer potential applications in related mathematical and applied contexts.